(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This of the article purpose Rheumatism the disease modern in medicine determination and treatment methods with get to know Modern of medicine this disease diagnosis and in prevention place about to understanding have to be , rheumatism the disease in treatment modern of medicine possibilities and importance analysis from doing consists of.